The Growth of Chlorella sp. Cultivated in Walne Media with Different Intensities of Light - Arafik Lamadi; Mulis Mulis; Agatha Elda Kristanto (Tomini Journal of Aquatic Science, 2022)
This research was composed to identify the effect of different light intensities on the growth of Chlorella sp, as well as the optimal amount of light to improve said growth. This experimental research employed completely randomized design, with 5 treatments of different light intensities; A (3400 lux), B (4400 lux), C (5400 lux), D (6400 lux) and E (7400 lux) with 4 replications for each treatment. Based on the ANOVA, the findings revealed the different effects of the treatments (p